2014
DOI: 10.1002/bjs.9551
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary exercise testing for the prediction of morbidity risk after rectal cancer surgery

Abstract: CPET can help predict morbidity after rectal cancer surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
76
3
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(83 citation statements)
references
References 24 publications
2
76
3
2
Order By: Relevance
“…The ability of CPET to identify patients at risk of poor outcomes is used clinically to guide perioperative care and clinical decision making, and it informs about the shared decision‐making process . We have previously reported that selected CPET variables such as oxygen uptake at estimated lactate threshold or anaerobic threshold ( trueV̇O 2 at AT) and at peak exercise ( trueV̇O 2 peak) are associated with worse outcome following colorectal surgery and neoadjuvant cancer treatments . Poor physical fitness is highly prevalent in HPB cancer patients and associated with poor post‐operative outcomes and survival …”
Section: Introductionmentioning
confidence: 99%
“…The ability of CPET to identify patients at risk of poor outcomes is used clinically to guide perioperative care and clinical decision making, and it informs about the shared decision‐making process . We have previously reported that selected CPET variables such as oxygen uptake at estimated lactate threshold or anaerobic threshold ( trueV̇O 2 at AT) and at peak exercise ( trueV̇O 2 peak) are associated with worse outcome following colorectal surgery and neoadjuvant cancer treatments . Poor physical fitness is highly prevalent in HPB cancer patients and associated with poor post‐operative outcomes and survival …”
Section: Introductionmentioning
confidence: 99%
“…morbidity, mortality, length of stay) [1][2][3][4][5][6][7][8][9][10][11][12]. Similar to immunological and neuroendocrine reserve, cardiorespiratory fitness indicates the physiological reserve capacity of the patient to maintain homeostasis with adequate responses to allostatic load (allostasis).…”
Section: Introductionmentioning
confidence: 99%
“…The time pressure experienced in the UK and internationally may well contribute to the lack of quality research and subsequent evidence base supporting the use of exercise treatments in the period between decision to treat and surgery for colorectal cancer. Given however, that recent work has shown that those with improved cardio-respiratory fitness have lower rates of mortality and complications following colorectal cancer surgery [8,9], this time period provides an opportunity to attempt to improve cardio-respiratory fitness before surgery, with the possibility of reducing peri-operative risk and improving post-operative outcome.…”
Section: Introductionmentioning
confidence: 99%